Caracterização da atividade suinícola desenvolvida pelos produtores familiares de queijo em Nossa Senhora da Glória, semiárido sergipano - Marinho, Glenda Lídice de Oliveira Cortez (2009)
The family farming system in the semi-arid region is observed in small productions, where the socioeconomic character composes a developed production system. In the high midland part of the estate of Sergipe, this system can be verified in the pig breeding developed associated with the cheese and milk fabrication and the cattle breeding in the municipal district of Nossa Senhora da Glória. The main characteristic of the areas in the city of Nossa Senhora da Glória is the subsistence agriculture, where the main activities are cheese and milk production and the breeding of pigs and other kinds of animals. The sustainable development of the production systems of the cheese producers of this region is related to the balance between the social, economical, ambiental and political institutional factors. To understand better the complex integration between the production sistems developed by the productors of Milk derivatives, this work studied the sustainability of the production systems of the cheese productors in Nossa Senhora da Glória, showing the related indexes under a new methodology represented by biograms and characterized the pig breeding developed in consortium with the milk processing units in the mentioned city, establishing the positives and negatives aspects in this production system.